The effect of video lecture types on the computational problem-solving performances of students - Selin Urhan; Selay Arkün Kocadere (Educational Technology & Society, 2024)
This study investigated the effect of video lecture types on the performance of students in computational problem-solving practices. A total of 19 university students participated in the computational problem-solving practices that mostly required declarative knowledge, and 22 university students participated in the computational problem-solving practices that mostly required procedural knowledge. The practices were implemented in the Algorithm and Programming course and the Computer Programming II course. Three video lecture types (instructor-whiteboard, instructor voice-handbook, instructor-slides) were used in both courses. The one-way repeated measures ANOVA test was employed to determine if there was a significant difference between the problem-solving performances of the students based on the video lecture type. In the Algorithm and Programming course that required mostly declarative knowledge, the problem-solving scores of the students were significantly higher after the instructor voice-handbook video practice than those after the instructor-whiteboard video practice. On the other hand, in the Computer Programming II course that required mostly procedural knowledge, the problem-solving scores of the students were significantly higher after the instructor-whiteboard video practice than those after the instructor voice-handbook video practice. The students showed higher performance in the video lecture types they preferred in both courses. The students listed the factors that affect their video preferences as (a) the effect of the presence of an instructor in the video lecture on their attention, (b) the efficiency of the video lecture in examining many and various examples in a limited time, (c) the opportunity provided by the video lecture to revise the content and procedure, and (d) the efficient presentation of the knowledge. It is recommended that an instructor should be present in the video that includes mostly procedural knowledge, while there is no need for an instructor in the video that includes mostly declarative knowledge regarding computational problem-solving activities.